Intracellular delivery of therapeutic antisense oligonucleotides targeting mRNA coding mitochondrial proteins by cell-penetrating peptides. Issue 47 (11th November 2020) - Cerrato, Carmine Pasquale; Kivijärvi, Tove; Tozzi, Roberta; Lehto, Tõnis; Gestin, Maxime; Langel, Ülo
Abstract : Development of a cell-penetrating peptide library to deliver biomolecules affecting mitochondria functionalities by targeting genes coding for mitochondrial proteins. Abstract : Cell-penetrating peptides are a promising therapeutic strategy for a wide variety of degenerative diseases, ageing, and cancer. Among the multitude of cell-penetrating peptides, PepFect14 has been preferentially used in our laboratory for oligonucleotide delivery into cells and in vivo mouse models. However, this activity has mainly been reported towards cytoplasm and nuclei, while the mentioned disorders have been linked to mitochondrial defects. Here, we report a library generated from a combinatorial covalent fusion of a mitochondrial-penetrating peptide, mtCPP1, and PepFect14 in order to deliver therapeutic biomolecules to influence mitochondrial protein expression. The non-covalent complexation of these peptides with oligonucleotides resulted in nano-complexes affecting biological functions in the cytoplasm and on mitochondria. This delivery system proved to efficiently target mitochondrial genes, providing a framework for the development of mitochondrial peptide-based oligonucleotide technologies with the potential to be used as a treatment for patients with mitochondrial disorders.